La historia del control de las administraciones públicas en la colonia (2005)
This article shows how government acts were controlled during the colonial period. Contrary with the principals authors of administrative law in Colombia that thought that the control began in the CC century with the implementation of the French model. Special emphasis is made on the distinction established on Hispanic Absolutist State between the competences of justice and government, before the French Revolution.